2010
DOI: 10.1128/aem.02717-09
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Vibrio anguillarum by Attached and Planktonic Roseobacter Cells

Abstract: The purpose of the present study was to investigate the inhibition of Vibrio by Roseobacter in a combined liquid-surface system. Exposure of Vibrio anguillarum to surface-attached roseobacters (107 CFU/cm2) resulted in significant reduction or complete killing of the pathogen inoculated at 102 to 104 CFU/ml. The effect was likely associated with the production of tropodithietic acid (TDA), as a TDA-negative mutant did not affect survival or growth of V. anguillarum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 40 publications
3
62
1
Order By: Relevance
“…To reduce the use of antibiotics, we and others have focused on use of probiotic strategies and used bacteria of the Roseobacter clade that can antagonize fish-pathogenic bacteria without harming the fish or their live feed (D'Alvise et al, 2012(D'Alvise et al, , 2013. Specifically, strains belonging to the species Ruegeria mobilis and Phaeobacter inhibens are potent antagonists of the fish pathogens (Planas et al, 2006;Porsby et al, 2008;D'Alvise et al, 2010) primarily caused by production of the antibacterial compound tropodithietic acid (TDA) (D'Alvise et al, 2010(D'Alvise et al, , 2012. TDA is also bactericidal against human pathogens including Salmonella enterica and Staphylococcus aureus (Porsby et al, 2011) and it has been recently been demonstrated that TDA acts by disrupting the proton motive force (Wilson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the use of antibiotics, we and others have focused on use of probiotic strategies and used bacteria of the Roseobacter clade that can antagonize fish-pathogenic bacteria without harming the fish or their live feed (D'Alvise et al, 2012(D'Alvise et al, , 2013. Specifically, strains belonging to the species Ruegeria mobilis and Phaeobacter inhibens are potent antagonists of the fish pathogens (Planas et al, 2006;Porsby et al, 2008;D'Alvise et al, 2010) primarily caused by production of the antibacterial compound tropodithietic acid (TDA) (D'Alvise et al, 2010(D'Alvise et al, , 2012. TDA is also bactericidal against human pathogens including Salmonella enterica and Staphylococcus aureus (Porsby et al, 2011) and it has been recently been demonstrated that TDA acts by disrupting the proton motive force (Wilson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several co‐culture studies of P. inhibens and V. anguillarum in axenic systems have shown significant inhibition of vibrios, resulting in lowered vibrio counts relative to the inoculum level (D'Alvise et al ., 2010, 2012; Grotkjær et al ., 2016b). In contrast, P. inhibens kept V. anguillarum at the inoculum level in both the non‐axenic co‐culture experiments conducted in the present study and in similar experiments with non‐axenic Tetraselmis and Artemia (Grotkjær et al ., 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that TDA-producing Roseobacter species have the ability to inhibit or kill other marine bacteria (3,13,22,41) and that purified TDA alone has a growth-inhibitory effect on marine bacteria (3). This study shows that TDA is a broad-spectrum antibacterial compound effective against all the human-pathogenic strains tested, in- Typhimurium strain harboring acrB, which encodes a multidrug efflux pump.…”
Section: Discussionmentioning
confidence: 99%
“…The killing or inhibitory effect is related to TDA production (3,22,41). Thus, D'Alvise et al previously showed that the fish-pathogenic bacterium Vibrio anguillarum strain 90-11-287 was killed only by TDA-producing wild-type Phaeobacter strain 27-4 and not by a mutant deficient in TDA production (13).…”
mentioning
confidence: 99%